The English Reading Comprehension, Skill, And Strategy of Senior High School Students - Mallipa, Imelda; Sitompul, Ester; Sitorus, Putri Ayu (Institut Agama Islam Negeri Palopo, 2024)
There is a demand for all students to be expert readers since today's life requires everyone to adapt to the fast development of technology and information that has changed the way information is presented. To help students acquire knowledge and skills in comprehending English written text, the intervention should be based on some considerations about the reading text, the students' characteristics, and the problems in comprehending a text. This study provides an investigation and analysis of the reading comprehension of senior high school students in two schools in Manokwari. There were 90 students as participants in this study. The students were given a 508-word expository text to be read. Six questions represented six reading comprehension skills were used to measure students' comprehension. The results were analyzed through the WINSTEPS computer package, Version 3.73, and explained using the Rasch model and reading comprehension models. The data showed that there were two reading comprehension skills are needed to be improved in all participants and the five basic skills demand intensive training for some participants. Some possible strategies to use for the future intervention process are discussed.